Top electrode for perovskite solar cell and perovskite solar cell
By inserting the Mo layer and filling the insulating material into the top electrode of the perovskite solar cell, the problem of low stability caused by the interaction between the top electrode and the perovskite absorbing layer is solved, and higher stability and performance are achieved.
Patent Information
- Application Number
- CN202411569101.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-18
AI Technical Summary
Perovskite solar cells have low stability due to the interaction between the top electrode and the iodine-containing compound decomposed by the perovskite absorption layer, and the perovskite absorption layer directly contacts the packaging material during laser scribe, resulting in instability.
A top electrode for perovskite solar cells is designed, including a first TCO layer, a Mo layer and a second TCO layer, and trenches are scribed on the top electrode to fill in an insulating material such as polyimide or SiO2 to improve the stability.
By inserting the Mo layer and filling the insulating material, the iodine ion exchange and metal atom diffusion are effectively blocked, which improves the stability and performance of perovskite solar cells and avoids unstable factors caused by laser scribing.
Smart Images

Figure CN119486462A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of perovskite solar cells, and in particular to a top electrode for a perovskite solar cell and a cell thereof. Background Art
[0002] The power conversion efficiency (PCE) of perovskite solar cells (PSCs) has reached 26.08%, which is comparable to that of silicon solar cells, making perovskite solar cells an ideal candidate for the next generation of photovoltaic power generation. However, its commercialization is still severely hindered by low device stability. In addition to the well-known thermal and chemical factors, another major cause of instability is the interaction between the top metal electrode and the iodine-containing compounds decomposed from the perovskite absorber layer. Both these volatile compounds and metal atoms can diffuse into each other through the carrier transport layer, resulting in a decrease in device performance. Another factor is that laser scribing of the metal electrode is required during the preparation of large-area components to divide them into small sub-cells to increase the device voltage, which will cause the perovskite absorber layer to directly contact the encapsulation material, causing device instability.
[0003] In order to solve the above problems, it is necessary to optimize the metal electrode and the perovskite absorption layer and insert an anti-corrosion layer that blocks the exchange of ions. Molybdenum is inherently resistant to the corrosion reaction between Mo and MoI because its metal-metal bond energy (435.5 kJ / mol) is higher than the metal-iodine bond energy (266.9 kJ / mol). In addition, theoretical analysis has also proved that Mo is stable to the diffusion of metal atoms into perovskite.
[0004] In order to solve the instability caused by laser scribing, insulating materials with mechanical properties can be filled in the laser grooves. Polyimide is a type of high-performance polymer film material developed in the past 10 years. It has a high temperature resistance of more than 400°C and a long-term use temperature range of -200 to 300°C. Some of them have no obvious melting point and high insulation performance. The dielectric constant is 4.0 at 103 Hz, and the dielectric loss is only 0.004 to 0.007, which belongs to F to H grade insulation.
[0005] For semi-transparent perovskite solar cells, in addition to conventional TCO electrodes, most use TCO and metal composite electrodes or alloy electrodes to improve the electron transmission of the battery. Patent CN117641967A discloses a perovskite device based on multilayer metal electrodes and its preparation method. The metal electrode layer is an aluminum, silver, gold, or copper metal electrode layer. The perovskite device with multilayer metal electrodes can not only reduce the impact of high temperature on the perovskite layer during metal evaporation deposition, but also optimize the interface contact between the perovskite layer and the electrode, which can effectively avoid short circuits of some devices caused by excessive current, optimize the energy level matching between the layers, and significantly improve the performance of the perovskite device. The device structure can be applied to devices such as light-emitting diodes and solar cells.
[0006] There are various attempts and methods to modify semi-transparent perovskite solar cells, but first of all, the impact of changing the electrode material on the light transmittance of the cell must be minimized. Secondly, the impact of the perovskite absorption layer on the stability of the device, which is directly in contact with the electrode and the external environment after being laser-etched after being prepared into a component, is not considered. Summary of the invention
[0007] A first aspect of the present invention provides a top electrode for a perovskite solar cell, wherein the top electrode for a perovskite solar cell comprises a first TCO layer, a Mo layer located above the first TCO layer, and a second TCO layer located above the Mo layer; and the top electrode for a perovskite solar cell is also provided with one or more grooves, wherein the grooves are filled with insulating material.
[0008] In one or more embodiments, the thickness of the first TCO layer is 30-50 nm.
[0009] In one or more embodiments, the Mo layer has a thickness of 5-10 nm.
[0010] In one or more embodiments, the thickness of the second TCO layer is 30-50 nm.
[0011] In one or more embodiments, the materials of the first TCO layer and the second TCO layer are selected from one or more of ITO, FTO and AZO.
[0012] In one or more embodiments, the width of the groove is 30-100 μm.
[0013] In one or more embodiments, the depth of the trench is 110-600 nm.
[0014] In one or more embodiments, the length of the groove is 10-2400 cm; preferably 10-400 cm.
[0015] In one or more embodiments, a plurality of the grooves are arranged in parallel at intervals on the top electrode for the perovskite solar cell.
[0016] In one or more embodiments, the insulating material is selected from polyimide and / or SiO2.
[0017] A second aspect of the present invention provides a method for preparing a top electrode for a perovskite solar cell as described in any embodiment of the present invention, the method comprising the following steps:
[0018] S1. sequentially preparing a first TCO layer, a Mo layer, and a second TCO layer on a substrate by one or more methods selected from the group consisting of evaporation, magnetron sputtering, printing, spin coating, blade coating, spray coating, spray pyrolysis, and slit coating;
[0019] S2. Use laser scribing to carve out grooves, and fill the grooves with insulating material.
[0020] In one or more embodiments, in step S1, a first TCO layer is formed on a substrate by magnetron sputtering, then a Mo layer is formed on the first TCO layer by magnetron sputtering, and finally a second TCO layer is formed on the Mo layer by magnetron sputtering.
[0021] In one or more embodiments, the laser scribing method is one or more of nanosecond infrared, picosecond green light, picosecond infrared, picosecond ultraviolet, femtosecond green light and femtosecond infrared.
[0022] In one or more embodiments, the filling is performed by deposition.
[0023] A third aspect of the present invention provides a perovskite solar cell, which comprises, from bottom to top, a substrate, a transparent conductive electrode, a hole transport layer, a perovskite absorption layer, an electron transport layer, and a top electrode for a perovskite solar cell as described in any embodiment of the present invention.
[0024] In one or more embodiments, the material of the transparent conductive electrode is selected from ITO or FTO.
[0025] In one or more embodiments, the transparent conductive electrode has a thickness of 200 nm to 800 nm.
[0026] In one or more embodiments, the material of the hole transport layer is selected from one or more of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, triphenylamine derivatives, non-triphenylamine nitrogen-containing small molecule materials, CuI, CuSCN, Cu2ZnSnS4, CuO, Cu2O, [2-(9H-carbazole-9-yl)ethyl]phosphonic acid and [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid.
[0027] In one or more embodiments, the hole transport layer has a thickness of 1 nm to 100 nm.
[0028] In one or more embodiments, the material of the perovskite absorption layer is Cs 0.25 FA 0.75 Pb(I 0.8 Br 0.2 )3.
[0029] In one or more embodiments, the perovskite absorber layer has a thickness of 450 nm to 550 nm and a band gap of 1.65 to 1.70 eV.
[0030] In one or more embodiments, the material of the electron transport layer is selected from one or more of TiO2, ZnO, WO3, SnO2, Zn2SnO4, fullerene and derivatives thereof.
[0031] In one or more embodiments, the thickness of the electron transport layer is 10 nm to 100 nm.
[0032] In one or more embodiments, the hole transport layer of the perovskite solar cell is provided with a groove for cutting off and dividing the hole transport layer and the transparent conductive electrode to expose the substrate; preferably, the width of the groove of the hole transport layer is 20 μm-50 μm; preferably, the groove of the hole transport layer is filled with perovskite material.
[0033] In one or more embodiments, the electron transport layer of the perovskite solar cell is provided with a groove for cutting and dividing the electron transport layer, the perovskite absorption layer and the hole transport layer to expose the transparent conductive electrode; preferably, the width of the groove of the electron transport layer is 50 μm-200 μm; preferably, the filling material of the groove of the electron transport layer is the same as the material of the top electrode for the perovskite solar cell as described in any embodiment of the present invention.
[0034] In one or more embodiments, the spacing between adjacent grooves of the hole transport layer and adjacent grooves of the electron transport layer is 200-300 μm.
[0035] In one or more embodiments, the spacing between adjacent grooves of the top electrode and the grooves of the electron transport layer is not greater than 100 μm.
[0036] In one or more embodiments, the perovskite solar cell comprises a plurality of sub-battery units, and the sub-battery units are arranged on the substrate to form an array arrangement of a single row in the length direction and n columns in the width direction; preferably, the width of the perovskite solar cell unit is 10mm-100mm, the length is 30mm-500mm, and the unit column spacing is 0.1mm-2mm.
[0037] A fourth aspect of the present invention provides the use of a top electrode for a perovskite solar cell as described in any embodiment herein in stabilizing a perovskite structure.
[0038] A fifth aspect of the present invention provides the use of a top electrode for a perovskite solar cell as described in any embodiment of the present invention in the preparation of a perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 It is a schematic structural diagram of a perovskite solar cell of the present invention.
[0040] Figure 2 Schematic diagram of the structure of the perovskite solar cell of Example 1.
[0041] Description of reference numerals:
[0042] Top electrode 1, first electron transport layer 2, second electron transport layer 3, perovskite absorption layer 4, hole transport layer 5, transparent conductive electrode 6, substrate 7, groove 8, groove 9, groove 10, Mo layer 11, first TCO layer 12, second TCO layer 13. DETAILED DESCRIPTION
[0043] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in this article. Unless otherwise specified, all technical and scientific terms used in this article are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definitions in this article shall prevail.
[0044] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0045] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.
[0046] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0047] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.
[0048] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.
[0049] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0050] In the present invention, transparent conductive oxide is referred to as TCO.
[0051] In the present invention, indium tin oxide is referred to as ITO for short.
[0052] In the present invention, fluorine-doped SnO2 is referred to as FTO.
[0053] In the present invention, aluminum-doped ZnO is referred to as AZO.
[0054] The purpose of the present invention is to provide a top electrode for a perovskite solar cell and a preparation method thereof. The top electrode of the present invention can enhance the stability of the perovskite and reduce the failure of the perovskite due to ion migration, thereby avoiding the failure of the component caused by stress generated by thermal pressure during the packaging process.
[0055] In some embodiments, such as Figure 1 As shown, the perovskite solar cell includes, from bottom to top, a substrate 7, a transparent conductive electrode 6, a hole transport layer 5, a perovskite absorption layer 4, a first electron transport layer 2, a second electron transport layer 3, and a top electrode 1 of the present invention. The top electrode 1 includes, from bottom to top, a first TCO layer 12, a Mo layer 11, and a second TCO layer 13; the top electrode is provided with a groove 10, and the groove 10 is filled with an insulating material.
[0056] The perovskite solar cell is also provided with grooves 8 and 9. The groove 8 is arranged on the hole transport layer 5, and is used to cut and separate the hole transport layer 5 and the transparent conductive electrode 6 to expose the substrate 7; the groove 8 is filled with the perovskite material. The groove 9 is arranged on the electron transport layer 2, and is used to cut and separate the electron transport layers 2 and 3, the perovskite absorption layer 4 and the hole transport layer 5 to expose the transparent conductive electrode 6, so that the top electrode 1 contacts the transparent conductive electrode 6 to form a current path. The filling material of the groove 9 is the same as that of the top electrode.
[0057] In the top electrode of the present invention, the thickness of the first TCO layer may be 30-50 nm.
[0058] In the top electrode of the present invention, the thickness of the Mo layer can be 5-10 nm;
[0059] In the top electrode of the present invention, the thickness of the second TCO layer may be 30-50 nm.
[0060] In the present invention, the material of the first TCO layer and the second TCO layer is selected from one or more of ITO, FTO and AZO. The material of the first TCO layer and the second TCO layer can be the same or different. In some embodiments, the material of the first TCO layer and the second TCO layer is the same, for example, ITO.
[0061] The present invention found that by optimizing the top electrode, an anti-corrosion layer that blocks iodine ion exchange is inserted between the TCO layers. Molybdenum is inherently resistant to the corrosion reaction of Mo and MoI because its metal-metal bond energy (435.5 kJ / mol) is higher than the metal-iodine bond energy (266.9 kJ / mol). In addition, theoretical analysis also proves that Mo is stable to the diffusion of metal atoms into perovskite.
[0062] The depth of the groove of the top electrode of the present invention is generally greater than the depth of the top electrode itself. In some embodiments, the depth of the groove is 110-600nm. In some embodiments, the length of the groove is 10-2400cm, such as 10-400cm. The length of the groove of the top electrode of the present invention is generally equal to the length of the battery.
[0063] In the top electrode of the present invention, the width of the groove may be 30-100 μm.
[0064] The groove of the top electrode of the present invention can be arranged on the right side of the groove of the electron transport layer (such as Figure 2 As shown), the spacing between the adjacent grooves of the top electrode and the grooves of the electron transport layer is not more than 100 μm. In some embodiments, the number of grooves of the top electrode and the number of grooves of the electron transport layer are equal. In some embodiments, the number of grooves of the top electrode is less than the number of grooves of the electron transport layer. In some embodiments, a plurality of grooves are arranged in parallel on the top electrode at intervals.
[0065] In the present invention, the insulating material may be selected from polyimide and / or SiO2.
[0066] The present invention finds that in order to solve the instability caused by laser scribing, an insulating material with mechanical properties such as polyimide or SiO2 can be filled in the laser groove. In some embodiments, the groove of the top electrode is filled with an insulating material such as polyimide or SiO2.
[0067] Polyimide is a type of high-performance polymer film material that has only been developed in the past 10 years. It can withstand high temperatures of over 400°C and has a long-term operating temperature range of -200 to 300°C. Some of them have no obvious melting point and have high insulation properties. The dielectric constant is 4.0 at 103 Hz and the dielectric loss is only 0.004 to 0.007, belonging to F to H grade insulation.
[0068] SiO2 is an excellent insulator with high resistivity and breakdown voltage, which can effectively prevent current leakage. Its melting point is as high as 1710℃. Moreover, SiO2 has excellent tolerance to most acids and alkalis. Except for hydrofluoric acid, it hardly reacts with other chemicals, which enables it to maintain its performance even in harsh chemical environments. The dielectric constant of SiO2 is about 3.4 (at 300K, 10kHz), which helps to reduce the capacitance effect in the circuit and improve the working speed and efficiency of the circuit. It has high hardness and wear resistance, and the thermal expansion coefficient is 0.5×10 -6 / K, which means that its dimensional stability is good when the temperature changes. It has good transparency in the visible light and near-infrared light regions, and has little loss to the optical structure of the battery; SiO2 is easy to process and can be made into thin films or coatings through various process methods. The material source is wide and the processing technology is mature, so it has certain cost advantages and is suitable for large-scale production.
[0069] The top electrode of the present invention can be obtained by coating a TCO material on a substrate (such as an electron transport layer) to form a first TCO layer, then coating Mo and TCO materials to form a Mo layer and a second TCO layer respectively, and then cutting grooves on the top electrode by laser scribing, and then filling the grooves with insulating material.
[0070] In some embodiments, the method for preparing the top electrode of the present invention comprises the following steps:
[0071] S1. sequentially preparing a first TCO layer, a Mo layer, and a second TCO layer on a substrate by one or more methods selected from the group consisting of evaporation, magnetron sputtering, printing, spin coating, blade coating, spray coating, spray pyrolysis, and slit coating;
[0072] S2. Use laser scribing to carve out grooves and fill the grooves with insulating material.
[0073] In some embodiments, the first TCO layer, the Mo layer, and the second TCO layer are sequentially prepared by magnetron sputtering.
[0074] In step S1 , the coating thicknesses of the first TCO layer, the Mo layer, and the second TCO layer may be adjusted according to the target thicknesses of the first TCO layer, the Mo layer, and the second TCO layer, respectively.
[0075] In step S2, the laser scribing method can be selected from one or more of nanosecond infrared, picosecond green light, picosecond infrared, picosecond ultraviolet, femtosecond green light and femtosecond infrared. In some embodiments, the laser scribing method is picosecond green light.
[0076] In step S2, the filling method may be a deposition method. In some embodiments, a mask is used to deposit the insulating material in the trench.
[0077] The present invention also includes a perovskite solar cell, which includes, from bottom to top, a substrate, a transparent conductive electrode, a hole transport layer, a perovskite absorption layer, an electron transport layer and a top electrode for the perovskite solar cell.
[0078] In some embodiments, in the perovskite solar cell of the present invention, the groove extends from the top electrode to the electron transport layer. In some embodiments, in the perovskite solar cell of the present invention, the groove extends from the top electrode to the perovskite absorption layer. The groove is used to separate the top electrode and play an insulating role.
[0079] The substrate material applicable to the present invention may be a conventional substrate material used in the art for preparing perovskite solar cells, such as a transparent glass substrate.
[0080] The material suitable for the transparent conductive electrode of the present invention can be selected from ITO or FTO. In the present invention, the preparation of the transparent conductive electrode is not particularly limited, and the conventional method for preparing the transparent conductive electrode in the art can be used, for example, a magnetron sputtering process is used to deposit it on the surface of the substrate. The process parameters can be adjusted according to the target thickness of the conductive oxide layer. In some embodiments, the thickness of the transparent conductive electrode is 200nm-800nm.
[0081] The material suitable for the hole transport layer of the present invention can be selected from one or more of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, triphenylamine derivatives, non-triphenylamine nitrogen-containing small molecule materials, CuI, CuSCN, Cu2ZnSnS4, CuO, Cu2O, [2-(9H-carbazole-9-yl)ethyl]phosphonic acid and [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid. The preparation of the hole transport layer is not particularly limited, and the conventional method for preparing the hole transport layer in the art can be used, such as a magnetron sputtering process. The process parameters can be adjusted according to the target thickness of the hole transport layer. In some embodiments, the thickness of the hole transport layer is 1nm-100nm.
[0082] The active material of the perovskite active layer suitable for the present invention contains ABX3 compounds, A is a monovalent cation, such as one or a mixture of monovalent cations of cesium, rubidium, methylamine, and methylamidine; B is a divalent cation, such as one or a mixture of divalent cations of lead, copper, zinc, gallium, tin, and calcium; X is a monovalent anion, such as one or a mixture of monovalent anions of iodine, bromine, chlorine, fluorine, and thiocyanate. In some embodiments, the material of the perovskite absorption layer is Cs 0.25 FA 0.75 Pb(I 0.8 Br 0.2)3. The preparation of the perovskite active layer is not particularly limited, and the conventional method for preparing the perovskite active layer in the art can be used, including but not limited to one or more of spin coating, blade coating, evaporation, printing, spraying, spray pyrolysis, and slit coating. The process parameters can be adjusted according to the target thickness of the perovskite absorber layer. In some embodiments, the thickness of the perovskite absorber layer is 450nm-550nm, and the band gap is 1.65-1.70ev.
[0083] Materials suitable for the electron transport layer of the present invention include, but are not limited to, one or more of C60, TiO2, ZnO, WO3, SnO2, Zn2SnO4, fullerene and its derivatives. The preparation of the electron transport layer is not particularly limited, and the conventional method for preparing the electron transport layer in the art can be adopted, including but not limited to one or more of spin coating, spray coating, spray pyrolysis, slit coating, and atomic layer deposition. The process parameters can be adjusted according to the target thickness of the electron transport layer. In some embodiments, the thickness of the electron transport layer is 10nm-100nm. In some embodiments, the electron transport layer includes a C60 layer and a SnO2 layer. Among them, the thickness of the C60 layer is 25-35nm; the thickness of the SnO2 layer is 10-20nm.
[0084] In the present invention, the hole transport layer of the perovskite solar cell may be further provided with a groove for cutting and dividing the hole transport layer and the transparent conductive electrode to expose the substrate; preferably, the width of the groove of the hole transport layer is 20 μm-50 μm. The groove may be scribed by laser scribing. The scribe line is a scribe line that separates the hole transport layer and the transparent conductive electrode without damaging the substrate.
[0085] In the present invention, the electron transport layer of the perovskite solar cell may also be provided with a groove for cutting off and dividing the electron transport layer, the perovskite absorption layer and the hole transport layer to expose the transparent conductive electrode so that the top electrode contacts the transparent conductive electrode to form a current path. In some embodiments, the line width of the groove of the electron transport layer is 50 μm-200 μm. The groove can be engraved by laser scribing. In some embodiments, the spacing between the grooves of the adjacent hole transport layer and the grooves of the electron transport layer is 200 μm-300 μm. In some embodiments, the spacing between the grooves of the adjacent top electrodes and the grooves of the electron transport layer is not more than 100 μm.
[0086] The perovskite solar cell of the present invention comprises a plurality of sub-cell units, which are arranged on a substrate to form an array arrangement of a single row in the length direction and n columns in the width direction. In some embodiments, the sub-cell unit of the perovskite solar cell has a width of 10 mm to 100 mm, a length of 30 mm to 500 mm, and a unit column spacing of 0.1 mm to 2 mm.
[0087] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The raw material compounds in the examples can all be purchased through commercial routes.
[0088] Example 1
[0089] (1) FTO (i.e., transparent conductive electrode) was prepared on a transparent glass substrate by magnetron sputtering with a thickness of 300 nm;
[0090] (2) NiOx (i.e., hole transport layer) was prepared by sputtering with a thickness of 30 nm;
[0091] (3) Using nanosecond infrared laser to scribe the glass coated with FTO and NiOx, a groove with a width of 30 μm and a depth of 500 nm was scribed, and the length was equal to the length of the battery;
[0092] (4) Depositing the perovskite light absorbing layer Cs on the NiOx layer by a one-step spin coating method 0.25 FA 0.75 Pb(I 0.8 Br0.2)3, band gap is about 1.68eV, thickness is 500nm;
[0093] (5) C60 is prepared by thermal evaporation method with a thickness of 30 nm; SnO2 is deposited by atomic layer deposition method with a thickness of 15 nm; and an electron transport layer containing a C60 layer + a SnO2 layer is obtained;
[0094] (7) Use picosecond green light to scribe on the SnO2 layer to create a groove with a width of 70 μm and a depth of 600 nm; the length is equal to the length of the battery;
[0095] (8) Preparation of top electrode by magnetron sputtering:
[0096] First, the first step is to sputter ITO to obtain the first TCO layer with a thickness of 50nm; then metal Mo is sputtered to obtain a Mo layer with a thickness of 10nm; finally, ITO is sputtered on the basis of the Mo layer to obtain the second TCO layer with a thickness of 50nm. The total thickness of the top electrode is 110nm, and the electrode preparation is completed;
[0097] Picosecond green light is used to scribe the top electrode to obtain a groove with a width of 50μm, a depth of 500nm, and a length equal to the length of the battery. Polyimide is deposited in the groove using a mask with a thickness of 500nm. The polyimide is filled in the groove. The battery is prepared. The schematic diagram of the prepared battery structure is shown below. Figure 2 shown.
[0098] Example 2
[0099] The only difference between Example 2 and Example 1 is that SiO2 is deposited in the groove of the top electrode using a mask plate with a thickness of 500 nm.
[0100] Comparative Example 1
[0101] The difference between Comparative Example 1 and Example 1 is that the top electrode is a bimetallic + Mo electrode, the first layer close to the electron transport layer is Cu, the middle layer is a Mo layer, and the top layer is Cu.
[0102] Comparative Example 2
[0103] The difference between Comparative Example 2 and Example 1 is that the trench of the top electrode is not filled with insulating material.
[0104] Test Example 1
[0105] The perovskite solar cells prepared in Examples 1-2 and Comparative Example 1 were subjected to photoelectric testing, the test light intensity was AM1.5G standard light intensity, the test temperature was 25±1° C., and the results were shown in Table 1 below:
[0106] Table 1. Photoelectric test results
[0107]
[0108]
[0109] Test Example 2
[0110] The perovskite solar cells prepared in Example 1 and Comparative Examples 1-2 were subjected to stability tests. The test light intensity was the AM1.5G standard light intensity, the test temperature was 25±1°C, and they worked continuously for 1000 hours at the maximum power point (mpp, mppt is maximum power point tracking, the instrument will automatically adjust the load size according to the current and voltage.). The retained initial efficiency of the battery in Example 1 was 97.5%. The retained initial efficiency of the battery in Comparative Example 1 was 87.0%. The retained initial efficiency of the battery in Comparative Example 2 was 68.5%.
[0111] The metal electrode of Comparative Example 1 is prone to metal corrosion, ion migration and interface reaction. Among them, the metal in Comparative Example 1 is prone to react with the perovskite, affecting the stability of the battery; under the action of the electric field, the ions in the metal electrode may diffuse into the perovskite layer, resulting in the decomposition of the perovskite material and the degradation of performance; the interface reaction between the metal electrode and the perovskite will produce deep energy level defects, which will become traps for carriers, increase non-radiative recombination, and thus reduce the efficiency and stability of the battery.
[0112] Since the grooves of the electrodes in Comparative Example 2 are not filled with insulating material, the craters caused by laser scribing may easily fall into the grooves during packaging lamination, thereby causing a short circuit. Therefore, the stability thereof is not better than that of the embodiment of the present invention.
[0113] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A top electrode for a perovskite solar cell, characterized in that: The top electrode for the perovskite solar cell includes a first TCO layer, a Mo layer located on the first TCO layer, and a second TCO layer located on the Mo layer; and the top electrode for the perovskite solar cell is also provided with one or more grooves, and the grooves are filled with insulating material.
2. The top electrode for a perovskite solar cell according to claim 1, characterized in that: The thickness of the first TCO layer is 30-50 nm; The thickness of the Mo layer is 5-10 nm; The thickness of the second TCO layer is 30-50 nm.
3. The top electrode for a perovskite solar cell according to claim 1, characterized in that: The materials of the first TCO layer and the second TCO layer are selected from one or more of ITO, FTO and AZO.
4. The top electrode for a perovskite solar cell according to claim 1, characterized in that: The top electrode for the perovskite solar cell has one or more of the following characteristics: The width of the groove is 30-100 μm; The depth of the groove is 110-600nm; The length of the groove is 10-2400 cm; A plurality of the grooves are arranged in parallel and at intervals on the top electrode for the perovskite solar cell.
5. The top electrode for a perovskite solar cell according to claim 1, characterized in that: The insulating material is selected from polyimide and / or SiO2.
6. A method for preparing a top electrode for a perovskite solar cell according to claim 1, characterized in that: The method comprises the following steps: S1. sequentially preparing a first TCO layer, a Mo layer, and a second TCO layer on a substrate by one or more methods selected from the group consisting of evaporation, magnetron sputtering, printing, spin coating, blade coating, spray coating, spray pyrolysis, and slit coating; S2. Use laser scribing to carve out grooves, and fill the grooves with insulating material.
7. The method for preparing a top electrode for a perovskite solar cell according to claim 6, characterized in that: In step S1, a first TCO layer is prepared on a substrate by magnetron sputtering, then a Mo layer is prepared on the first TCO layer by magnetron sputtering, and finally a second TCO layer is prepared on the Mo layer by magnetron sputtering.
8. The method for preparing a top electrode for a perovskite solar cell according to claim 6, characterized in that: The laser scribing method is one or more of nanosecond infrared, picosecond green light, picosecond infrared, picosecond ultraviolet, femtosecond green light and femtosecond infrared; and / or The filling method is a deposition method.
9. A perovskite solar cell, characterized in that: The perovskite solar cell comprises a substrate, a transparent conductive electrode, a hole transport layer, a perovskite absorption layer, an electron transport layer and a top electrode for a perovskite solar cell according to any one of claims 1 to 5, which are arranged in sequence from bottom to top. 10.Select from the following applications: Use of the top electrode for a perovskite solar cell according to any one of claims 1 to 5 in stabilizing the perovskite structure; Use of the top electrode for a perovskite solar cell as claimed in any one of claims 1 to 5 in the preparation of a perovskite solar cell.
Citation Information
Patent Citations
Perovskite device based on multilayer metal electrode and preparation method thereof
CN117641967A
Cited By
Perovskite solar cell module with high conversion efficiency
CN122514133A
Perovskite solar module and manufacturing method thereof
TWI892949B